PENGARUH MODAL DAN PENINGKATAN PENJUALAN TERHADAP LABA USAHA STUDI KASUS PADA KEYO COFFEE DI PAL V KECAMATAN KOTA BARU (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to determine the effect of Capital and Sales Increase on Operating Profit either simultaneously or partially. The sample in this study is Keyo Coffee. Hypothesis testing using multiple linear regression analysis with the help of the SPSS program. The results showed that the variables of Capital and Sales Increase had a positive and significant effect on Operating Profit. Partially, capital has no effect on operating profit. While partially, the Sales Increase variable has a positive and significant effect on Operating Profit. The influence given by the independent variable on the dependent variable Is 91,5%.